Increased levels of nectin-4 as a serological marker for pre-eclampsia - Hikari Yoshizawa; Haruki Nishizawa; Mayuko Ito; Akiko Ohwaki; Yoshiko Sakabe; Takao Sekiya; Takuma Fujii; Hiroki Kurahashi (Fujita Medical Journal, 2023)
Objectives: Nectin-4 is a cell adhesion molecule with vital functions at adherens and tight junctions. Cumulative evidence now indicates that the NECTIN4 gene is overexpressed in a variety of cancers, and that the nectin-4 protein is both a disease marker and therapeutic target in a subset of these cancers. We previously demonstrated that NECTIN4 is overexpressed in placenta during pre-eclamptic pregnancy, which is one of the most serious obstetric disorders.